2020
DOI: 10.1186/s12983-020-00379-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of Tarim red deer (Cervus elaphus yarkandensis) reveals demographic history and adaptations to an arid-desert environment

Abstract: Background The initiation of desert conditions in the Tarim Basin in China since the late Miocene has led to the significant genetic structuring of local organisms. Tarim Red Deer (Cervus elaphus yarkandensis, TRD) have adapted to the harsh environmental conditions in this basin, including high solar radiation and temperature, aridity, and poor nutritional conditions. However, the underlying genetic basis of this adaptation is poorly understood. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 93 publications
(141 reference statements)
1
15
0
Order By: Relevance
“…The divergence time of Yarkand hare (0.86 Mya) estimated herein is in agreement with the results obtained from mitochondrial genes (0.83 Mya [ 8 ]; 0.84 Mya [ 83 ]), combined with numerous accurate fossil datasets. Notably, this divergence time is similar to that of other species currently living around the Tarim Basin, including Cervus elaphus yarkandensis (0.8–2.2 Mya [ 73 ]; 0.98 Mya [ 84 ]), and with the timing of the most recent common ancestor Phrynocephalus axillaris (0.88 Mya) and the appearance of Phrynocephalus forsythii in the Tarim Basin (0.94 Mya) [ 85 ].…”
Section: Discussionsupporting
confidence: 65%
“…The divergence time of Yarkand hare (0.86 Mya) estimated herein is in agreement with the results obtained from mitochondrial genes (0.83 Mya [ 8 ]; 0.84 Mya [ 83 ]), combined with numerous accurate fossil datasets. Notably, this divergence time is similar to that of other species currently living around the Tarim Basin, including Cervus elaphus yarkandensis (0.8–2.2 Mya [ 73 ]; 0.98 Mya [ 84 ]), and with the timing of the most recent common ancestor Phrynocephalus axillaris (0.88 Mya) and the appearance of Phrynocephalus forsythii in the Tarim Basin (0.94 Mya) [ 85 ].…”
Section: Discussionsupporting
confidence: 65%
“…It would also be interesting to look at sequence divergence between red deer and sika for each of the 45 genes that we have identified here. While there is a sika genome ( Xing et al 2021 ) and a Hungarian red deer genome ( Ababaikeri et al 2020 ), neither of these is from Scottish red deer nor Scottish sika, which would be ideal for comparing divergence within this system, particularly given that introgression is occurring and selection is possible. Additionally, future work could look at gene expression at these genes to estimate whether expression differences are correlated with carcass mass ( Todd et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other methods can be applied to a single desert population and identify genomic regions of reduced diversity, skewed allele frequency distribution, increased haplotype homozygosity (haplotype-based) [14,15], or combinations thereof, all of which could be signatures of selective sweeps [9,10]. These approaches have been used to detect selection in different desert-dwelling mammals [12,13,[16][17][18], and we highlight some specific examples herein.…”
Section: Population-specific Desert Adaptationmentioning
confidence: 99%
“…Several studies of different desert mammals have identified genes, and functional classes of genes and pathways, involved in fat metabolism [17,21,32,39,55], thyroid-induced metabolism [12], salt metabolism and prevention of high blood pressure [13,16,34], insulin signaling Box 1. Endurer-Evader-Evaporator Concept Aiming to summarize and categorize decades of classic literature on desert adaptations in species occupying distinct ecological niches, Willmer et al [2] proposed a classification system relative to extreme temperatures and body size.…”
Section: Convergent Evolution At the Genetic Levelmentioning
confidence: 99%
See 1 more Smart Citation